2022
DOI: 10.3390/nu14051014
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Composition of Human Milk Oligosaccharides Correlates with Effects on Both the Intestinal Epithelial Barrier and Host Inflammation: A Pilot Study

Abstract: Background: Human milk oligosaccharides are complex, non-digestible carbohydrates that directly interact with intestinal epithelial cells to alter barrier function and host inflammation. Oligosaccharide composition varies widely between individual mothers, but it is unclear if this inter-individual variation has any impact on intestinal epithelial barrier function and gut inflammation. Methods: Human milk oligosaccharides were extracted from the mature human milk of four individual donors. Using an in vitro mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…For instance, glycans provide sialic acid needed for the baby’s brain development . About 70–83% of all sialic acid present in human milk is bound with HMOs, 14–28% with glycoprotein glycans and 0.2–0.4% with glycolipids (primarily gangliosides). , In addition, oligosaccharides act as a metabolic substrate to shape the intestinal flora, serve as antiadhesive antimicrobials, and modulate epithelial and immune cell responses, thereby contributing to immune protection. , And N -glycans simultaneously contribute to antibacterial, antiviral, and immune system regulation, , and O -glycans affect the formation and stability of the intestinal microbiota and act as effective decoy receptors for pathogenic gastrointestinal bacteria and viruses . The different glycans consumed in early life are suggested to be associated with differences in long-term health conditions and intelligence between breastfed and bottle-fed infants. Hence, insights into the composition and variation of oligosaccharides and N / O -glycans in babies’ early life are urgently needed for the innovation and improvement of infant formula.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, glycans provide sialic acid needed for the baby’s brain development . About 70–83% of all sialic acid present in human milk is bound with HMOs, 14–28% with glycoprotein glycans and 0.2–0.4% with glycolipids (primarily gangliosides). , In addition, oligosaccharides act as a metabolic substrate to shape the intestinal flora, serve as antiadhesive antimicrobials, and modulate epithelial and immune cell responses, thereby contributing to immune protection. , And N -glycans simultaneously contribute to antibacterial, antiviral, and immune system regulation, , and O -glycans affect the formation and stability of the intestinal microbiota and act as effective decoy receptors for pathogenic gastrointestinal bacteria and viruses . The different glycans consumed in early life are suggested to be associated with differences in long-term health conditions and intelligence between breastfed and bottle-fed infants. Hence, insights into the composition and variation of oligosaccharides and N / O -glycans in babies’ early life are urgently needed for the innovation and improvement of infant formula.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to human subjects, AF has also been shown to reduce gut inflammatory processes and NEC severity in mice [ 34 ] and preterm pigs [ 41 ]. Porcine or human AF decreased intestinal inflammatory cytokines and increased body weight [ 42 ], inviting speculation that HMOs account for these effects of AF, similar to direct HMO effects observed in vitro [ 22 , 23 , 43 ]. Thus, our findings may be valuable for developing future preventive approaches for infants at risk of VLBW.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have suggested that sialylated HMOs, potentially by providing sialic acid as building block for brain gangliosides, promote neuronal and brain development and might have long-lasting effects on the development of cognitive functions [ 20 , 21 ]. Moreover, several studies have suggested HMO effects on intestinal barrier function, mucosal immune maturation and neonatal intestinal development [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…HMOs can adjust the intestinal epithelial cells as a signal molecule reaction. Wu and co-workers used the intestinal injury model induced by EHEC O157:H7 to evaluate the effect of HMOs on the intestinal epithelial barrier and the selection of innate and adaptive immune functions . The research showed that HMOs could prevent changes in the integrity of the intestinal epithelial barrier and macromolecular permeability induced by pathogens.…”
Section: Hmos As a New Potential Food Bioactive Componentmentioning
confidence: 99%
“…The research showed that HMOs could prevent changes in the integrity of the intestinal epithelial barrier and macromolecular permeability induced by pathogens. After exposure to different HMOs, the host cell signal transduction response and the expression of innate and adaptive immune responses were different . HMOs can also regulate chemical barriers composed of mucus layers.…”
Section: Hmos As a New Potential Food Bioactive Componentmentioning
confidence: 99%